Natalia Taccetta, Dalla segnatura all’avanguardia. Agamben e Benjamin fra rovina e collezione (ENTHYMEMA, 2019)
Translation of: Taccetta, Natalia, “Signatura e historia: una aproximación al encuentro Benjamin-Agamben”, Metahistorias, 2011. The aim of this article is to discuss the relation between Benjamin and Agamben in defining the Avant-guard as aesthetic and cognitive phenomenon.
Keywords: Agamben; Benjamin; avant-guard; signature; collection